The Absence of Mother’s Love Experienced by the Main Female Character in Jacqueline Wilson’s The Story of Tracy Beaker - Bernadia Puspa Damayanti; Ratna Asmarani (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
This research thesis discusses Jacqueline Wilson’s The Story of Tracy Beaker about Tracy Beaker, a ten years old girl living in a children’s home waiting for her mother to pick her up. The purpose of this study is to discover the causes and impacts of the absence of the mother’s love for the main character, Tracy Beaker. The writer uses psychological methods and close reading methods with characters, conflict, and setting theories for the intrinsic elements and John Bowlby’s attachment theory for the extrinsic elements. The result of the research indicates that the main character, Tracy Beaker, has increased aggression, delinquency, and affectionless psychopathy because she is abandoned by her biological mother.Keywords: Jacqueline Wilson; love; attachment